Epidemiologia e diferentes métodos de diagnóstico na identificação de bovinos leiteiros com tuberculose, paratuberculose e leucose enzoótica bovina - Souza, Mariana Assunção de (2018)
Tuberculosis (TB), paratuberculosis (PTB) and enzootic bovine leukosis (EBL) are diseases that affect the dairy herd and cause several losses in production. In the second chapter, the performance of a commercial ELISA TB test was evaluated in dairy herds. A total of 1644 cows were examined by the comparative cervical tuberculin test (CCTT) and 846 in a commercial kit of ELISA M. bovis IDEXX. Positives cattle in ELISA M. bovis were analyzed in macroscopic, histological and microbiological/PCR tests. Of the 1644 bovines, 80 (4.8%) were positive in CCTT and 4,25% (36/846) in ELISA M. bovis, 35 negative and one inconclusive in CCTT. Of the 36 positives in ELISA M. bovis, 27 were euthanized. Lesions suggestive of TB were identified in three carcasses on macroscopic test, and in two cases were confirmed by histological, microbiological / PCR methods. The low association of ELISA with the results obtained in macroscopic, histological and isolation, points to the fragility of the ELISA performance in field conditions. In the third chapter we investigated the intercurrence of PTB in bovines reagents in CCTT of TB. For this, 334 cattle were evaluated by CCTT, ELISA TB and ELISA PTB. Viscera fragments from the positives in CCTT were collected and evaluated by qPRC M. bovis and PTB PCR. 16 cattle were reactive in CCTT. In these, no macro or microscopic lesions suggestive of TB were identified, and the presence of DNA of M. bovis in qPCR was also not detected. However, in 9 animal samples (9/16), the DNA of M. avium subsp. paratuberculosis (MAP) was indentified, and in 12 carcasses (12/16) lesions characteristic of PTB were visualized, which were confirmed by histopathological methods. Antibodies Anti-MAP were detected in seventeen and anti-M. bovis in other nine animals of the herd. MAP infection may have caused nonspecific reactions in tuberculin test. In the fourth chapter, the epidemiological situation of PTB and BEL was investigated in dairy herds of Lagoa Formosa - MG. 40 herds were selected and 236 samples were collected, and submitted to ELISA PTB and agar gel immunodiffusion (AGID) for BEL. Prevalence for PTB was 20% (95% CI: 7,60% – 32,39%) for herds and 6% (95% CI: 2,98% – 9,02%) for animals. Prevalence of BEL was 85% (95% CI: 82.16% - 87.84%) for herds and 50.42% (95% CI: 49,51% - 51,32%) for animals. The presence of PTB was associated with: age (OR = 0,088), creation of calves with adults (OR = 41.45) and contact of calves with feces of adult animals (OR = 5.008). BEL was associated with blood transfusion (OR = 2.32), veterinary assistance (OR = 2.61) and natural mount (OR = 2.27). It was concluded that 6% of the bovines presented evidence of infection caused by MAP and 50.42% by BLV. It is suggested that farmers and veterinarians take greater care in adopting sanitary measures for these diseases, incorporating surveillance elements based on the risks identified in the study.